Projekt statutu kapelana zakładu leczniczego oraz domu pomocy społecznej. Podstawy i uzasadnienie - Bartoszek, Antoni (Warszawskie Studia Teologiczne, 2023)
The article presents a draft of a statute of the chaplain of a care facility and a nursing home. This is a suggestion grounded in scientific reflection carried out in four steps. The first step analyses and presents a social-ecclesial context of the ministry of a chaplain and the way the status is drafted. The second step formulates anthropological, theological and legal grounds that are a starting point for creation of the draft. The third step covers a synthetic analysis of the legal status which is the basis for the draft. Step four, that is the most essential one, presents concrete norms that might be included in the statute. The main part the article presents a full version of the draft of the status accompanied by an explanation and rationale behind the formulated norms.